New scholarship in religion and United States empire. Issue 5 (16th April 2019) - Dougherty, Matthew W.
Abstract: The last few decades have seen an immense expansion in the range of topics included in the field of American religion. The methodologies and overarching narratives of the field have, however, remained more static. Despite the inclusion of racialized minorities, women, and non‐Christians in American religious history, the field has still tended to endorse a liberal integrationist narrative that minimizes the distinct positions of these and other groups in American religious life. New research conducted under the rubric of "religion and U.S. empire" offers one possible way forward for the field by reorienting narratives about American religion toward the study of how colonial systems produce terms such as religion, freedom, and pluralism. This new approach not only foregrounds the stories of colonized peoples but also allows their experiences to reframe how we narrate American religious history. This article discusses the background of the study of empire in U.S. history and religious studies, provides an overview of the main theoretical interventions of works in religion and U.S. empire, and concludes with a discussion of possible future directions for research in this field.